"Shock Therapy" in Ukraine: A Radical Approach to Post‐Soviet Police Reform. (May 2016) - Peacock, Robert; Cordner, Gary
Summary: Ukraine has pursued an aggressive "shock therapy" approach to police reform since early 2015, in the aftermath of the February 2014 Maidan protests and subsequent change of government. This approach is described and examined in light of previous 21st century post‐Soviet police reform efforts in Ukraine, Georgia, and Kyrgyzstan. Internal and external pressures to demonstrate real commitment to corruption control and rule of law seem to have been responsible for pushing Ukraine in the direction of the Georgian shock therapy model. Early results are very promising, but significant challenges remain, including sustaining the reform political coalition, overcoming bureaucratic resistance to change, surviving the armed insurgency in eastern Ukraine, downsizing the old militsiya, reshaping the culture of corruption that permeates the entire government and much of society, and convincing the citizenry that the new police are truly committed to serving the public, not regime protection. Copyright © 2016 John Wiley & Sons, Ltd.